Kinetic-energy release of fragments from electron-impact dissociation of the molecular hydrogen ion and its isotopologues - Scarlett, L.; Zammit, M.; Fursa, Dmitry; Bray, Igor (American Physical Society, 2017)
We calculate the kinetic-energy release distributions of fragments produced for electron-impact dissociation of the vibrationally excited molecular hydrogen ion H2+ and its isotopologues D2+ and T2+. Here we apply the adiabatic-nuclei convergent close-coupling method and compare results with several different methods, including the δ approximation. Results are presented for a number of dissociative excitation transitions and dissociative ionization as a function of the initial vibrational state of the molecule. We confirm that the square root approximation is a good approximation for the adiabatic-nuclei kinetic-energy release cross sections of H2+. Agreement with experiment, where available, is good.